Evidence of an Effect of Gaming Experience on Visuospatial Attention in Deaf but Not in Hearing Individuals - Holmer, Emil; Rudner, Mary; Schönström, Krister; Andin, Josefine (Frontiers in Psychology, 2020)
Auditory cortex in congenitally deaf early sign language users reorganizes to support cognitive processing in the visual domain. However, evidence suggests that the potential benefits of this reorganization are largely unrealized. At the same time, there is growing evidence that experience of playing computer and console games improves visual cognition, in particular visuospatial attentional processes. In the present study, we investigated in a group of deaf early signers whether those who reported recently playing computer or console games (Deaf Gamers) had better visuospatial attentional control than those who reported not playing such games (Deaf Non-gamers), and whether any such effect was related to cognitive processing in the visual domain. Using a classic test of attentional control, the Eriksen Flanker task, we found that Deaf gamers performed on a par with hearing controls, while the performance of Deaf Non-gamers was poorer. Among hearing controls there was no effect of gaming. This suggests that deaf gamers may have better visuospatial attentional control than deaf non-gamers, probably because they are less susceptible to parafoveal distractions. Future work should examine the robustness of this potential gaming benefit and whether it is associated with neural plasticity in early deaf signers, as well as whether gaming intervention can improve visuospatial cognition in deaf people.